Grolier Programmed English Course: Book 4 - Margaret Maggs; Anna Veltfort (USA Grolier International, Inc., 1983)
Previously Published as Programmed English: A Self-Instructional Course
Cassettes Tape Kept Separately at The Audio-Visual Service. Audiocassettes
Keywords: Languages (3GddZGJs; General; English language; Conversation Patterns; Study and teaching; Foreign speakers; Textbooks for foreign speakers